Studying the role of periplasmic chaperones in Fab presentation on phage surface. - Lim , Theam Soon
In phage display technology, antibodies presented on phage particles are often a smaller variant of the antibody molecule. The Fab format consists of a pair of heavy chain and light chain that is linked together via a disulphide bridge. The low presentation efficiency of Fab (fragment antigen binding) fragments during phage display is largely due to the complexity of disulphide bond formation